Integration of the computational fluid dynamics technique with MRI in aortic dissections. Issue 5 (14th June 2012) - Karmonik, Christof; Partovi, Sasan; Davies, Mark G.; Bismuth, Jean; Shah, Dipan J.; Bilecen, Deniz; Staub, Daniel; Noon, George P.; Loebe, Matthias; Bongartz, Georg; Lumsden, Alan B.
Abstract Short‐term and long‐term prognosis and their determining factors of Type III/Stanford B aortic dissections (TB‐AD), which separate the aorta distal at the origin of the subclavian artery into a true lumen and false lumen, have been elusive: One quarter of patients thought to be treated successfully, either by medical or by surgical means, do not survive 3 years. Unfavorable hemodynamic conditions are believed to lead to false lumen pressure increases and complications. A better characterization of TB‐AD hemodynamics may therefore impact therapeutic decision making and improve outcome. The large variations in TB‐AD morphology and hemodynamics favor a patient‐specific approach. Magnetic resonance imaging with its capability to provide high‐resolution structural images of the lumen and aortic wall and also to quantify aortic flow and kinetics of an exogenous tracer is a promising clinical modality for developing a deeper understanding of TB‐AD hemodynamics in an individual patient. With the information obtained with magnetic resonance imaging, computational fluid dynamics simulations can be performed to augment the image information. Here, an overview of the interplay of magnetic resonance imaging and computational fluid dynamics techniques is given illustrating the synergy of these two approaches toward a comprehensive morphological and hemodynamic characterization of TB‐AD. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.